KiDS-i-800: Comparing weak gravitational lensing measurements from same-sky surveys - Amon, A; Heymans, C; Klaes, D; Erben, T; Blake, C; Hildebrandt, H; Hoekstra, H; Kuijken, K; Miller, L; Morrison, C; Choi, A; De Jong, J; et al. (Oxford University Press, 2018)
We present a weak gravitational lensing analysis of 815 deg2of i-band imaging from the Kilo-Degree Survey (KiDS-i-800). In contrast to the deep r-band observations, which take priority during excellent seeing conditions and form the primary KiDS data set (KiDS-r-450), the complementary yet shallower KiDS-i-800 spans a wide range of observing conditions. The overlapping KiDS-i-800 and KiDS-r-450 imaging therefore provides a unique opportunity to assess the robustness of weak lensing measurements. In our analysis we introduce two new 'null' tests. The 'nulled' two-point shear correlation function uses a matched catalogue to show that the calibrated KiDS-i-800 and KiDS-r-450 shear measurements agree at the level of 1 ± 4 per cent.We use five galaxy lens samples to determine a 'nulled' galaxy-galaxy lensing signal from the full KiDS-i-800 and KiDS-r-450 surveys and find that the measurements agree to 7 ± 5 per cent when the KiDS-i-800 source redshift distribution is calibrated using either spectroscopic redshifts, or the 30-band photometric redshifts from the COSMOS survey.